Temperature uniformity evaluation of a shuttle kiln for the sanitary ware industry using CFD. Issue 6 (1st November 2020) - Romero-Flores, Michel; Tapia-Martínez, Alejandro D.; Mariella-González, Karlo; Cantú-Pérez, Alberto; Montesinos-Castellanos, Alejandro
Abstract : Shuttle kilns are widely used in the sanitary ware industry. A key parameter to reduce energy consumption and increase their overall performance is temperature uniformity. Therefore, in this paper a systematic and statistical study of the effect of the position of burners and their interactions on the temperature uniformity of a shuttle kiln is performed. CFD simulations and a 4k factorial analysis were used to determine, quantitatively and qualitatively, the best burner configuration in hterms of kiln temperature uniformity. It was found that the proximity of the burners has a negative impact on the temperature distribution of the kiln. These proximities caused collisions of the burners streams which deflected the flow in the Y -axis direction. This may increase the outlet velocity of the combustion gases, diminishing the heat exchange between gases and the ceramic pieces, producing a heterogeneous distribution of temperature. The standard deviation varied from 2.29 to 3.78 depending of the configuration of the burners used. To avoid these negative effects, collisions between the streams of the burners should be avoided. Also, the distance between the furniture carts of the kiln could be varied to maximise the heat exchange inside. The results obtained are useful in the design of ceramic shuttle kilns, as it allows one to determine the quantitative and qualitative effect of the position of the burners at different sections of the kiln.